Operating Scheme of The Combined Unit Implementing The Resource-Saving Technology of Soil Working - A. N. Khudoyarov, A. N. Khudoyarov; I.I. Abdimominov, I.I. Abdimominov; M.A. Yuldasheva, M.A. Yuldasheva; A. Yoldashev, D. Mominova (Indonesian Journal Publisher, 2024)
The article presents the results of a study of the movement scheme of a combined unit that implements resource-saving technology of soil cultivation. At the same time, the aggregate is loosened in one pass with an interval of 1800 mm between the rows, forming two fertilized rows, and four rows of rows with an interval of 90 cm are formed in the return.